2017
DOI: 10.1088/1361-6560/aa58c8
|View full text |Cite
|
Sign up to set email alerts
|

Towards standardization of x-ray beam filters in digital mammography and digital breast tomosynthesis: Monte Carlo simulations and analytical modelling

Abstract: In digital breast tomosynthesis and digital mammography, the x-ray beam filter material and thickness vary between systems. Replacing K-edge filters with Al was investigated with the intent to reduce exposure duration and to simplify system design. Tungsten target x-ray spectra were simulated with K-edge filters (50μm Rh; 50μm Ag) and Al filters of varying thickness. Monte Carlo simulations were conducted to quantify the x-ray scatter from various filters alone, scatter-to-primary ratio (SPR) with compressed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
7
0
2
Order By: Relevance
“…This limits the utility of an increase in tube voltage in order to increase photon fluence. Shrestha et al (Shrestha et al 2017) also performed analytical calculations of SDNR to examine whether the change from K-edge to Al filtration had a detrimental effect on image quality. For all three schemes described earlier, use of Al filtration enabled the SDNR of the K-edge filtered case to be matched, but with reduced exposure duration and some reduction in mean glandular dose (MGD).…”
Section: X-ray Sourcementioning
confidence: 99%
“…This limits the utility of an increase in tube voltage in order to increase photon fluence. Shrestha et al (Shrestha et al 2017) also performed analytical calculations of SDNR to examine whether the change from K-edge to Al filtration had a detrimental effect on image quality. For all three schemes described earlier, use of Al filtration enabled the SDNR of the K-edge filtered case to be matched, but with reduced exposure duration and some reduction in mean glandular dose (MGD).…”
Section: X-ray Sourcementioning
confidence: 99%
“…Figure 5 shows standard bremsstrahlung spectra from a molybdenum anode. Monte Carlo simulations and analytical modelling (Shrestha et al 2017) have indicated that roughly 1 mm of aluminum, as used in these studies, provides good filtration for DBT when tungsten anodes are used. Longer term plans for this technology include cladding the molybdenum focal tracks with a tungsten/rhenium alloy, commonly employed outside of breast imaging applications for general purpose radiography and computed tomography.…”
Section: X-ray Spectramentioning
confidence: 82%
“…Tests were carried out to verify the usability of the system in the routine, adding Ag (silver) and Cu (copper) filters, for the characterization of attenuated radiation beams of interest in diagnostic radiology [9,10].…”
Section: Discussionmentioning
confidence: 99%